To Give or to Forgive? Aid versus Debt Relief - Cordella, Tito; Missale, Alessandro (2012)
Is generalized debt relief an effective development strategy, or should assistance be tailored to countries' characteristics? To answer this question, the authors build a simple model in which recipient governments reveal their creditworthiness if donors offer them to choose between aid and debt relief. Since offering such a menu is costly, it is preferred by donors only when the cost of assistance is low, and the probability that an indebted country is creditworthy is high enough. For lower probabilities and higher costs of assistance, donors prefer a policy of only debt relief. Very limited aid is the preferred policy only for high costs of assistance, and low probabilities that the government is creditworthy.